Identification of rye chromosomes by flow cytogenetics - Alkhimova, O.G.; Zimina, O.V. (Вiopolymers and Cell, 2017)
The karyotype of the cultivated rye (Secale cereale) is one of the complex plant genomes whose chromosomes are difficult to discriminate because of their similar size. Aim. The purpose of this study is to reveal the chromosome variable sites using DNA repetitive sequences as probes and to define a possibility of sorting rye chromosomes. Methods. Flow cytometry analysis and karyotyping, chromosome sorting, fluorescence in situ hybridization and microscopy. Results. Different distribution of repetitive DNA sites between two rye accessions was demonstrated and an ability to sort chromosome 1 in the ‘Zhyttedaine’ rye variety was shown. This is the second case when chromosome 1R was sorted by flow cytometry in S. cereale. Conclusions. The present study revealed chromosome polymorphisms of microsatellite sequence GAA in accessions and the potential of chromosome sorting in S. cereale varieties. We also identified sequence elements including microsatellites and classic satellites which can be utilized for future research and in rye breeding.